Assessment of the hydrological status of Doñana dune ponds: a natural World Heritage Site under threat. Issue 15 (10th December 2018) - Fernández-Ayuso, A.; Rodríguez-Rodríguez, M.; Benavente, J.
ABSTRACT: The hydrological response of shallow ponds to groundwater withdrawal has been of growing concern in the Doñana National Park (southern Spain) in recent decades. This study examines the role of groundwater in maintaining the hydroperiod (i.e. the hydrological regime) in the park's main dune ponds, by quantifying the groundwater fluxes to/from them. The hydrological characterization was performed by applying different methodologies. Daily hydrological balances registered in the ponds revealed groundwater contributions ranging from 80% of the total water inflows (i.e. groundwater discharge) to a net groundwater recharge from the ponds to the aquifer, and enabled the studied water bodies to be classified as discharge or recharge systems. The recharge systems must have been influenced by the lowering of piezometric levels due to groundwater extraction for urban supply in a nearby coastal resort.